Analisis Strategi Penghimpunan Infaq Melalui Media Digital QRIS di SMA Pertiwi 1 Padang - Erika Marianti; Ghima Septia Putri; Muhamad Rishan; Aisyah Hariyani; Adira Nuraisyah (Universitas Negeri Padang, 2023)
In the 21st century, technological developments have progressed not only in the world of work but also in the world of education. The use of technological media is not only limited to the teaching and learning process, but must also be able to penetrate into other activities such as infaq. Therefore this study has several objectives, namely to find out the use of QRIS in collecting infaq, to ​​find out what motivates the school to use QRIS, and to find out how effective it is in using QRIS. This study uses qualitative research with a type of field research (Field Research) with a descriptive approach. The data source used in this study was by conducting direct interviews with several informants by preparing several questions related to the research object. The data collection technique used was direct observation and interviews with the school principal and PAI teachers. After the interview process was carried out, the transcript process of the interview data was then carried out to then take themes that were in accordance with the objectives. Overall, the research findings found six important themes related to the analysis of infaq collection through QRIS digital media, namely: i) Production motivation, ii) Constraints to use, iii) Strengths, iv) Weaknesses, v) Effectiveness of use, vi) Targets and expectations. The results of this research can be used as a basis or reference for future research, to investigating similar problems in different contexts and issues.